Bibliometrics of Latin American research on COVID-19 in the first year of the pandemic: the main trends - Chiu, Wen-Ta Ta (2021)
Introduction: An outbreak of the COVID-19 was appended in the central Chinese city of Wuhan in December 2019. Lots of related papers were published in the world since then. Objective: This study aimed to identify and analyze the characteristics of COVID-19 publications in the Science Citation Index Expanded (SCI-EXPANDED) published by Latin Americans in 2020. Methods: Documents including searching keywords in their title, abstract, or author keywords from SCI-EXPANDED were assessed. The analyzed aspects covered characteristics of document types, languages, Web of Science categories, and journals. Publication performances of countries and institutions were evaluated by six publication indicators and two citation indicators. Results: A lower percentage of articles and a higher percentage of Spanish language were found. Web of Science category of general and internal medicine published the most articles. The Clinics was the most popular journal. The Cadernos de Saude Publica and Revista da Associacao Medica Brasileira published the most publications and reviews, respectively. Brazil took a leading position in the six publication indicators. The University of São Paulo in Brazil was the most productive institution. Based on the number of citations from the Web of Science Core Collection since publication to the end of 2020, 10 most frequently cited publications were presented. In addition, the analysis of words in publication titles, author keywords, and KeyWords Plus was performed to find the main research focuses. Conclusions: In 2020, a total of 3 056 COVID-19 documents in SCI-EXPANDED were published by Latin Americans mainly in the Web of Science categories of ‘general and internal medicine’ and ‘public, environmental and occupational health’. More letters and editorial materials and fewer articles were published in the first year of its outbreak. A higher percentage of Spanish and Portuguese publications was found. Brazil dominated the six publication indicators. The University of São Paulo in Brazil ranked top in all the six publication indicators while the Technological University of Pereira in Colombia had a higher impact for their first- and corresponding-author publications. Health and infection were the main research focuses.